Rab25 increases cellular ATP and glycogen stores protecting cancer cells from bioenergetic stress - Cheng, Kwai Wa (WILEY-VCH Verlag, 2012)
Cancer cells are metabolically stressed during tumour progression due to limited tumour vascularity and resultant nutrient, growth factor and oxygen deficiency that can induce cell death and inhibit tumour growth. We demonstrate that Rab25, a small GTPase involved in endosomal recycling, that is genomically amplified in multiple tumour lineages, is a key regulator of cellular bioenergetics and autophagy. RAB25 enhanced survival during nutrient stress by preventing apoptosis and autophagy via binding and activating AKT leading to increased glucose uptake and improved cellular bioenergetics. Unexpectedly, Rab25 induced the accumulation of glycogen in epithelial cancer cells, a process not previously identified. Strikingly, an increase in basal ATP levels combined with AKT-dependent increases in glucose uptake and glycogen storage allowed maintenance of ATP levels during bioenergetic stress. The clinical relevance of these findings was validated by the ability of a Rab25-dependent expression profile enriched for bioenergetics targets to identify patients with a poor prognosis. Thus, Rab25 is an unexpected regulator of cellular bioenergetics implicated as a useful biomarker and potential therapeutic target.